PROSES PELIPUTAN BERITA â€œLINTAS PAGIâ€ RRI SEMARANG DALAM PERSPEKTIF KOMUNIKASI ISLAMI - Ardani, Ahdini Rizqi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2018)
Radio is an auditive communication media with several characteristics, among them is a crosshairs and contain interference. Listening to radio programs can only be done once. One of the radio programs is news. Dissemination of information and news via radio can take place quickly and wider. Broadcast news on the radio must be true, once the news is wrong in broadcast it is not possible to repeat again. Because the listener may only hear the error, do not hear what is rectified. It may also be that the listener did not hear the error, so that the wrong message rectified is correct. In the context of Islamic communication spreading good, true, and honest news is a must. Islamic communication is a way of communicating that is Islamic, which is not contrary to the teachings of the Qur'an and Hadith.This study aims to describe the news coverage process